2021
DOI: 10.3390/children8020082
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Preschool Hours in Achieving Physical Activity Recommendations for Preschoolers

Abstract: Research on physical activity (PA) in different educational settings could elucidate which interventions promote a healthy school lifestyle in early childhood education (ECE). The aims of this study were: (a) to analyse the PA levels of preschoolers during school hours, as well as the rate of compliance with specific recommendations on total PA (TPA) and moderate-vigorous PA (MVPA); (b) to examine the role of structured movement sessions and recess time in the MVPA levels during school hours; (c) to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 47 publications
1
18
0
Order By: Relevance
“…In particular, playing outdoors requires social support and parental supervision [ 80 ]. In addition, because parental restrictions can prevent participation in PA and outdoor play in preschoolers [ 81 ], our data reinforce the importance of external and internal space for active play at home, since most of the responsibility for promoting healthy behaviors and PA practices currently falls on families [ 82 ].…”
Section: Discussionsupporting
confidence: 59%
“…In particular, playing outdoors requires social support and parental supervision [ 80 ]. In addition, because parental restrictions can prevent participation in PA and outdoor play in preschoolers [ 81 ], our data reinforce the importance of external and internal space for active play at home, since most of the responsibility for promoting healthy behaviors and PA practices currently falls on families [ 82 ].…”
Section: Discussionsupporting
confidence: 59%
“…However, further studies are necessary to analyse specifically how MVPA is modulated by the different curricular practices (structured/unstructured PA opportunities, the role of the teacher, free/instructed play, among others) and by the location where these practices are performed (indoors/outdoors). In any case, following Lahuerta-Contell et al [ 32 ], reaching the recommended levels of MVPA during school time requires further efforts to encourage less active children—with a particular eye on gender differences—to increase intensity during their curricular activities. For instance, Carson et al [ 31 ] have found that sedentary time and MVPA in educators may be an important correlation of MVPA in toddlers during child care hours [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…In line with its findings (i.e., an association between SB and classroom density), indoor environmental characteristics, such as the ‘modified open-plan space’, are positively associated with PA in toddlers, so providing enough spaces for playing likely keeps children engaged and active [ 27 ]. Indeed, a high density of preschoolers was associated with higher levels of SB during school hours [ 32 ]. Overall, it is possible that larger classrooms and/or lower student/teacher ratios could decrease SB and keep children active.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, many studies focus on investigating how to enhance motor or activity skills in childhood education. For instance, Scholars [16] used Palestine to explore which intervention measures can improve children's health conditions in school life through physical activity among preschool children in different educational circumstances. The results found that preschool children rarely engage in total physical activity and moderatevigorous physical activity when in class.…”
Section: Introductionmentioning
confidence: 99%